UNIQUE ASPECTS OF OBJECT AND DOCUMENT EXAMINATION IN CRIMINAL INVESTIGATIONS (World Bulletin of Management and Law, 2024)
This article analyzes the specific features of examining objects and documents, their differences from other investigative actions, and the purpose and objectives of conducting an examination. It also discusses the problems that arise while examining objects and documents and ways to solve them. Based on the results obtained, recommendations for improving the examination of objects and documents have been developed.
Keywords: examination of objects and documents; investigative action; evidence